Development of potent HLA-A02:01-restricted peptide-based cytotoxic T-cells against SARS-CoV-2 infections in patients awaiting a kidney transplant - Chang, Chih-Chao; Liu, Ya Nan; Xu, Zheng; Vasilescu, Elena-Rodica; Li, Ping; Ho, Eric K.; Li, Muyang; Husain, Syed A.; Bhagat, Govind; Mohan, Sumit; Vlad, George; Suciu-Foca, Nicole (Frontiers in Immunology, 2025)
BackgroundControlling viral infections prior to solid organ transplantation is vital for successful engraftment and overall well-being of patients. One promising approach involves the deployment of viral antigen-specific cytotoxic T cells to eradicate viral pathogens. Although there have been attempts to develop anti-viral vaccines in the literature, the limited number of virus-specific cells which can be generated in vitro in the autologous system make it impracticable for autologous therapy.MethodsWe developed a straightforward and scalable method for the in vitro expansion of SARS-CoV-2 Spike S1 peptide-specific cytotoxic CD8+ T cells. This was achieved through combinatorial stimulation with S peptide-conjugated polystyrene microspheres in the presence of cytokines IL-2, IL-7, and IL-15 for 14 days.ResultsUsing A2/S269-specific tetramers as markers, we compared induction of S-specific CD8+ T cells from patients awaiting kidney transplantation (n=67) with that of normal controls (n=65). We found that this method has the potential to achieve at least a 10-fold up to 200-fold increase in S-specific CD8+ T cells in 34.3% of kidney transplant candidates and 36.9% of normal controls, respectively. These SARS-CoV-2 specific CD8+ T cells released inflammatory cytokines, expressed effector-memory T cells markers, and killed target cells in a dose-dependent and antigen-specific manner.ConclusionOur study demonstrates that viral antigen-specific cytotoxic CD8+ T cells can be robustly enriched in vitro from peripheral blood mononuclear cells of both healthy individuals and patients with kidney diseases using peptide-conjugated microspheres. Our findings provide novel insights into a potential therapeutic approach, using autologous anti-viral CD8+ T cells for transplant recipients/candidates.